Forecasting travel time reliability in road transport: A new model for the Netherlands - Marco Kouwenhoven; Pim Warffemius (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
In this paper we describe how we included travel time variability in the national Dutch transport forecasting model and what the policy impacts of this new forecasting tool are. Until now, travel time reliability improvements for road projects were included in Dutch cost-benefit analysis (CBA) by multiplying the travel time benefits from reduced congestion by a factor 1.25. This proportionality is based on the linkage between congestion reduction and reliability improvements. However, this treatment of reliability is not useful to evaluate policies that especially affect travel time variability. From the start, this method was provisional and meant to be replaced by a better method capturing travel time variability. For this, we derived an empirical relation between the standard deviation of travel time, mean delay of travel time and length of route. This has been implemented in the national Dutch model as a post processing module. The new travel time reliability forecasting model will be incorporated in the Dutch guidelines for CBA.
Keywords: 330; Straßenverkehr; Transportzeit; Rationalität; Verkehrsökonomik; Niederlande